2006
DOI: 10.1002/ijc.21723
|View full text |Cite
|
Sign up to set email alerts
|

The norepinephrine‐driven metastasis development of PC‐3 human prostate cancer cells in BALB/c nude mice is inhibited by β‐blockers

Abstract: The development of metastases is a decisive step in the course of a cancer disease. The detection of metastases in cancer patients is correlated with a poor prognosis, and over 90% of all deaths from cancer are not due to the primary tumor, which often can be successfully treated, but are due to the metastases. Tumor cell migration, a prerequisite for metastasis development, is not merely genetically determined, but is distinctly regulated by signal substances of the environment including chemokines and neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
240
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(267 citation statements)
references
References 22 publications
22
240
0
4
Order By: Relevance
“…Use of a1 receptor blockers has already been shown to reduce the probability of developing prostate cancer, 73 and b blockers reduce NE-driven metastasis in a rodent model. 74 Another study concludes that b blockers may produce a general decrease in cancer risk, 75 and a second study found a decrease in prostate cancer rate with b blocker use. 76 On the other hand, a few studies have shown that use of b blockers either has no effect on the rate of breast cancer 77,78 or may even increase it.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of a1 receptor blockers has already been shown to reduce the probability of developing prostate cancer, 73 and b blockers reduce NE-driven metastasis in a rodent model. 74 Another study concludes that b blockers may produce a general decrease in cancer risk, 75 and a second study found a decrease in prostate cancer rate with b blocker use. 76 On the other hand, a few studies have shown that use of b blockers either has no effect on the rate of breast cancer 77,78 or may even increase it.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…These drugs may also help treat existing cancers since some cancerous cells have functional adrenoceptors. [60][61][62][63]74,80 As described earlier, reducing the activation of some adrenoceptor subtypes by lowering the level of NE or via a or b blocking drugs may actually increase carcinogenesis rather than decrease it, 79 and this may vary for different organs. And when examining whether NE drugs affect cancer rates, it is not only important to compare people who are taking these drugs for a condition such as hypertension with healthy control subjects (some of whom may be taking these drugs), but also with hypertensive people taking classes of drugs that do not affect the NE system.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…calf serum ( FCS ; Hyclone ), penicillin and streptomycin ( Invitrogen ) at 37 ° C and 5 % CO 2 . PC3 luc expressing a fi refl y luciferase can be used for living imaging 35 . PC3 luc cells were cultured in RPMI1640 in 10 % FCS, penicillin and streptomycin at 37 ° C and 5 % CO 2 .…”
Section: E N T I -V E C T O R L E N T I -V E C T O R Kdamentioning
confidence: 99%
“…However, the uncertain role of the immune system in regulating solid tumor growth led us to consider an alternative hypothesis: stress mediators from the sympathetic nervous system might directly regulate the growth and metastatic potential of tumor cells, independent of the effects on the immune system [17]. Recently, there is growing evidence confirming that alterations in neuroendocrine dynamics due to chronic stress can cause alterations in tumor pathogenesis [17][18][19][20][21]. In this review, we will focus on these biological pathways that may be affected by stress mediators.…”
Section: Introductionmentioning
confidence: 99%